Facial Nerve Paralysis in a Bitch after Surgery: Recovery with Acupuncture - Pedro Antônio de Oliveira; Henrique de Castro, Pedro; Júlia Rocha Bicalho, Yasmin; Valle Pereira, Gabriella; Aoki Heredia, Daniela; da Silva Gonçalves, Fernanda; Magno do Vale Barroso, Rogério; David Solis Murgas, Luis (Acta Scientiae Veterinariae, 2026)
Background: Facial nerve (7th cranial nerve) paralysis in dogs is associated with several etiologies, including direct trauma, otitis media, intracranial neoplasms, and encephalitis. Clinical signs of facial paralysis include ear and lip ptosis, increased palpebral fissure, hypersalivation, decreased palpebral reflex, reduced or absent spontaneous blinking, absence of nostril abduction during inspiration, and facial spasms. This study aimed to report the case of an 8-year-old female Pinscher that developed facial nerve paralysis following an ablative procedure performed at the Veterinary Hospital of the Federal University of Lavras, in Lavras, MG, and was subsequently treated with acupuncture. Case: A treatment regimen consisting of vitamin B12 and lubricating eye drops had been prescribed for at-home administration. After 8 days of vitamin B12 treatment without clinical improvement, acupuncture was proposed as an alternative therapy by veterinary acupuncturist Fernanda da Silva Gonçalves. Upon evaluation, the patient presented with left eyelid hyporeflexia; absence of voluntary movement and auricular reflex on the left side; and facial asymmetry due to left-sided lip ptosis. Based on the clinical findings, an acupuncture protocol was established, initially consisting of 10 sessions using the following points for 15 min per session: B1 (nourishes Yin Qi, increases water energy, improves vision, disperses Wind, and reduces pathological Tai Yang Heat), B2 (improves vision and disperses Wind and Heat), ST4 (regulates Qi circulation and removes Qi obstruction in the energy channels, enhances facial muscle Qi, and disperses Wind and Cold from Yang Ming), ST6 (harmonizes Qi, strengthens the teeth and jaw, improves Qi flow in the temporomandibular joint, removes Qi obstructions in the energy channels, disperses pathological Wind and Cold, clears Heat, and relaxes facial muscles), GV20 (maintains body Yang, disperses excess Yang from the Yang energy channels, stabilizes the ascent of Yang Qi, calms Shen and emotions, clears the mind, restores consciousness, and relaxes tendons and muscles), GV24-1 (clears the mind and vision, eliminates Heat, disperses Wind-Heat, and promotes revival), GB20 (enhances vision, nourishes the brain, harmonizes excess Yang Qi, improves joint function, expels pathogenic energies, promotes blood circulation, removes Qi obstructions in the energy channels, relaxes muscles and tendons, and disperses Wind, Wind-Cold, and Wind-Heat), and TE23 (improves vision, clears Heat from the head and face, and disperses Wind and Heat). Discussion: The facial paralysis observed in the bitch in this case affected voluntary movement of the left hemiface, with clinical signs including loss of facial expression due to the absence of auricular and labial movement, as well as the inability to close the eyelid. In unilateral facial nerve paralysis, facial asymmetry is evident, along with muscle tone loss and ear and/or lip ptosis on the affected side. In previously reported cases, the most common cause has been damage to branches of the facial nerve passing through the middle ear, secondary to inflammation, infection, neoplasia, or traumatic injury either at the brainstem level or peripherally, as the nerve traverses the temporal bone. In such cases, acupuncture may be beneficial through its effects on stimulating nerve activity in the skin and muscles via needle insertion, thereby promoting local blood and Qi flow to affected vessels and supporting tissue nutrition for muscle movement recovery. In this case, rapid improvement of clinical signs and complete recovery of the patient were observed after 8 acupuncture sessions. Thus, acupuncture proved to be an effective technique for treating facial nerve paralysis. Keywords: facial paralysis, acupuncture, veterinary. Título: Paralisia de nervo facial em uma cadela após cirúrgia: recuperação com acupuntura Descritores: medicina tradicional chinesa, nervo facial, terapia por acupuntura.